Prevalence and associated factors of non-consensual sexual acts among adolescents in the Democratic Republic of Congo - Yode, Miangotar; Ekofo, Felly; Mudekereza Mihigo, Blaise (Frontiers in Reproductive Health, 2024)
IntroductionDuring adolescence, due to lack of experience, individuals may engage in or tolerate certain non-consensual acts under coercion. There are significant associations between forced sexual intercourse and a range of negative effects on reproductive health, as well as psychological and emotional health. Studies on non-consensual sexual acts among adolescents are rare in the Democratic Republic of Congo (DRC). This study is one of the first to focus on urban adolescents, aiming to assess the prevalence of non-consensual sexual acts and to identify associated factors.MethodsData for this study were obtained from the baseline survey of the project “Reducing the Vulnerability of Adolescents and Young Girls to Violence and HIV/AIDS Infection,” conducted in 2018 in the provinces of Kinshasa and Kasaï Oriental among adolescents aged 10-24 years. A total of 2,123 adolescents were surveyed (46.8% in Kinshasa and 53.2% in Kasaï Oriental). A structured survey questionnaire was developed in French to collect data. This questionnaire was pre-tested and corrected before use. Non-consensual sexual acts were assessed using three variables: (i) Have you ever experienced non-consensual touching, (ii) Have you ever experienced an attempted forced sexual intercourse, and (iii) Have you ever been physically forced, injured, or threatened to have sexual intercourse. Bivariate and multivariate analyses were conducted on these three variables separately.ResultsAmong all adolescents surveyed, 11.5% reported having experienced non-consensual touching, 15.3% reported having experienced an attempted forced sexual intercourse, and 5.8% reported having been physically forced, injured, or threatened to have sexual intercourse. Among the 575 sexually active adolescents, these proportions were 43.4%, 57.4% and 22.0%, respectively. Prevalences were higher among girls and in the province of Kinshasa. Factors associated with non-consensual sexual acts included gender, cohabitation with biological parents (father and mother), age at first sexual intercourse, communication about sexuality or intimate subjects with a family member, and adolescents' perceptions of the role and place of partners in intimate relationships. A quarter (25.5%) of adolescents who were victims of forced sexual intercourse and were aware of an appropriate institution or person sought help from a professional for the violence they experienced.DiscussionThe results revealed a high prevalence of non-consensual sexual acts, the significance attributed by adolescents to traditional beliefs regarding the dominant role of men in intimate relationships, and the existence of barriers preventing victims of sexual violence from seeking appropriate care. These findings advocate for providing healthcare services tailored to the needs of adolescents and adapted to sociocultural contexts.